Literacy Analysis in Facing the Era of Society 5.0 Through PAI Learning in State MTs 1 Prabumulih City - Ersi Ersi; Cittra Juniarni; Dwi Noviani (World Journal of Islamic Learning and Teaching, 2025)
The Society 5.0 era integrates digital technology with human values to create a human-centered society that addresses social issues, enhances quality of life, and promotes sustainability. Digital literacy and multidimensional skills are crucial in education to prepare students for global challenges. Strengthening literacy in reading, numeracy, science, finance, digital competence, and citizenship is key to adaptation and progress. However, literacy levels in Indonesia, including at MTs Negeri 1 Kota Prabumulih, require improvement to foster critical thinking and knowledge application. Based on multiliteracy and multidimensional theories, literacy development extends beyond text comprehension to include interactions with cultural, social, and technological contexts for meaningful learning. This qualitative study with a phenomenological approach explores students' literacy levels, relevant literacy concepts for Society 5.0, the integration of Islamic Education (PAI) values with literacy, and how PAI supports literacy enhancement at MTs Negeri 1 Kota Prabumulih. Data were collected through interviews, observations, and documentation. The results indicate that students' literacy levels remain moderate, requiring enhancement. Literacy integration with PAI is evident in thematic approaches, linking zakat to financial literacy and Qur'anic verses to science. However, optimizing facilities, teacher training, and project-based learning is necessary for stronger literacy development.